Heat exposure during outdoor activities in the US varies significantly by city, demography, and activity. (November 2018) - Hoehne, Christopher G.; Hondula, David M.; Chester, Mikhail V.; Eisenman, David P.; Middel, Ariane; Fraser, Andrew M.; Watkins, Lance; Gerster, Katrina
Abstract: Environmental heat is a growing public health concern in cities. Urbanization and global climate change threaten to exacerbate heat as an already significant environmental cause of human morbidity and mortality. Despite increasing risk, very little is known regarding determinants of outdoor urban heat exposure. To provide additional evidence for building community and national-scale resilience to extreme heat, we assess how US outdoor urban heat exposure varies by city, demography, and activity. We estimate outdoor urban heat exposure by pairing individual-level data from the American Time Use Survey (2004–2015) with corresponding meteorological data for 50 of the largest metropolitan statistical areas in the US. We also assess the intersection of activity intensity and heat exposure by pairing metabolic intensities with individual-level time-use data. We model an empirical relationship between demographic indicators and daily heat exposure with controls for spatiotemporal factors. We find higher outdoor heat exposure among the elderly and low-income individuals, and lower outdoor heat exposure in females, young adults, and those identifying as Black race. Traveling, lawn and garden care, and recreation are the most common outdoor activities to contribute to heat exposure. We also find individuals in cities with the most extreme temperatures do not necessarily have the highest outdoor heat exposure. The findings reveal large contrasts in outdoor heat exposure between different cities, demographic groups, and activities. Resolving the interplay between exposure, sensitivity, adaptive capacity, and behavior as determinants of heat-health risk will require advances in observational and modeling tools, especially at the individual scale. Highlights: 11.5 years of weather and time-use data are combined for 50 US urban regions. Metabolic intensity data are included to estimate intensity of heat exposure. Outdoor heat exposure is higher in the elderly, males, and low income individuals. Outdoor heat exposure is lower in young adults and those identifying as Black race. Cities with the most extreme heat do not necessarily have higher heat exposure.